Computational experiments on the study of the motion of celestial bodies - Mukushev, B.A. (Recent Contributions to Physics, 2023)
It is difficult to overestimate the role and place of computational experiments in modern scientific research. Scientists investigate physical phenomena based on computer models and computational experiments when analytical methods of theoretical physics do not allow obtaining more reliable results. On the other hand, computational experiments can be carried out in conditions inaccessible to field experiments. The paper presents the scientific results of the study of some issues of celestial mechanics. These results are obtained on the basis of the use of computer methods. The MathCAD application software package is used as a programming language. The main scientific results include the following: a graph of the potential of the gravitational field of the Earth is constructed depending on the distance r to the center of the Earth; on the basis of a computer approach, the equations of the potential energy (binding energy) of the interaction of a body of a unit mass with the Earth-Moon system are studied; on the basis of computer methods, graphs are obtained. These graphs characterize the binding energies of the body depending on the coordinates of the radial axis; with the help of the MathCAD package, the flight path of the spacecraft near the Earth was modeled under various initial conditions; the motion of the spacecraft from the Earth to the Moon was studied and various types of flight paths were constructed depending on its initial velocity.